EFEKTIVITAS MODEL PEMBELAJARAN ARCS UNTUK MENINGKATKAN MOTIVASI BERPRESTASI DI KALANGAN SISWA YANG BERASAL DARI STATUS EKONOMI RENDAH (Jurnal Bimbingan dan Konseling Islam, 2015)
The motivation to achieve among students from low economic status is low and frequently at a concerning level. To increase their motivation to achieve, an appropriate learning model can be implemented. One of the learning models that can increase the motivation to achieve is ARCS learning model. The research aims to increase the motivation to achieve among students from low economic status and to find the difference in the levels of motivation between students from low economic status treated and not treated with ARCS learning model. The research employed a quasi-experimental design. It was conducted by taking 60 twelfth grade students of SMA (Senior High School) Daarul Ilmi Cipeundey as the sample, distributing them into experimental and control classes, with a number of 30 students for each class. The twelfth grade students in the experimental class were treated with ARCS learning model, and those in the control class were not treated with ARCS learning model. The results of t-test showed that tcount 9.572 > ttable 2.002 at the significance level of 0.000 < 0.05; hence, H0 was rejected, and Ha was accepted. This value means that there was a significant difference in the gain scores between the experimental class and the control class. Based on these results, the researcher recommends that training on ARCS model should be given to teachers, and future researchers are recommended to take a larger sample size.